Project Lib understanding how librarians in Metro Manila manage their projects - Moraña, Mark F. (School of Library and Information Studies, University of the Philippines, Diliman, 2019)
As libraries continue to grow and evolve, librarians explore new ideas, introduce new products and create new services that will make them adapt, thrive and stay relevant in today's world. They are the continuously undertaking projects to achieve their goals. The application of project management (PM) concepts and approaches offers a standardized way of managing these projects. Given that the technological aspect of most librarian job continues to grow, and technology-based projects in libraries require expertise from across the library, PM is and will remain an important aspect of library management (Kinkus, 2007).